2019
DOI: 10.31983/jnj.v3i1.4536
|View full text |Cite
|
Sign up to set email alerts
|

Health Education Using the Leaflet Media Reduce Anxiety Levels in Pre Operation Patients

Abstract: Background: Surgery will cause anxiety. One way to reduce anxiety in preoperative patients is through health education using leaflet media. Leaflets are pieces of paper that contain writing and images to convey a message and are easy to carry. Purpose: This study was to analyze the effect of health education using leaflet media on anxiety levels in preoperative patients at Ungaran Hospital. Methods: This study used Quasi-Experiment with the design of two group pre-post. Bivariate analysis using the Wilcoxon te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…This study showed that most of the respondents were employees and was supported by the research of Rizki and Hartoyo (2019) who found that the majority of respondents' jobs were employees. This was different from the research of Usnadi, Rahayu, and Praptiwi (2019) where the majority of respondents were housewives.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study showed that most of the respondents were employees and was supported by the research of Rizki and Hartoyo (2019) who found that the majority of respondents' jobs were employees. This was different from the research of Usnadi, Rahayu, and Praptiwi (2019) where the majority of respondents were housewives.…”
Section: Discussionsupporting
confidence: 64%
“…This difference was due to the majority of respondents in this study. The type of job that has an unstable income can affect the behavior of respondents in determining treatment, buying medicine, paying hospital costs, and paying high medical costs which will increase respondents' anxiety (Rizki & Hartoyo, 2019). Similar results were also conducted by Vellyana, Lestari, and Rahmawati (2017) who stated that anxiety can be triggered by low-income levels and economic status.…”
Section: Discussionmentioning
confidence: 54%
“…The intervention group has been shown to decrease anxiety compared to before the health education was given. The provision of health education using leaflet media can be used as an alternative for presenting information to prepare patients before surgery to decrease anxiety levels (19). Hence, Hsueh stated that education is necessary for patients with a certain characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Tindakan bedah menempati urutan ke-11 dari 50 penanganan pola penyakit di rumah sakit se-Indonesia dengan persentase 12,8%. 3 Data lain menunjukkan bahwa 11% beban penyakit di dunia dapat ditanggulangi dengan pembedahan. 3 Kementerian Kesehatan telah menunjuk 110 rumah sakit rujukan regional, 20 rumah sakit rujukan provinsi, dan 14 rumah sakit rujukan nasional.…”
Section: Pendahuluanunclassified